2016
DOI: 10.3892/etm.2016.3162
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role of microRNA-30b and plasminogen activator inhibitor-1 in the pathogenesis of cognitive impairment

Abstract: Abstract. The present study aimed to investigate the role of plasminogen activator inhibitor-1 (PAI-1) in drug-induced early cognitive impairment and the underlying mechanism concerning microRNA (miR)-30b. A mouse model of cognitive impairment was established by intraperitoneal injection of scopolamine (2 mg/kg body weight) for 13 days. Behavioral performance was assessed using the Morris water maze (MWM) test. The mRNA expression levels of PAI-1 and miR-30b were detected using quantitative polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…44 Through analysis with CCK-8 and flow cytometry, augmented proliferation and attenuated apoptosis were determined in femoral vein endothelial cells when miR-335-5p expression was up-regulated and PAI-1 expression was down-regulated. MiR-335-5p has been reported to be involved in cell differentiation and apoptosis of osteoblasts in diabetic osteoporosis, 47 In addition, miR-335 has the ability to influence apoptosis and invasion in non-small cell lung cancer, 48 and clear cell renal cell cancer proliferation and invasion by inhibiting the expression of BCL-W. 49 Meanwhile, PAI-1 is proved to be an apoptosis-related biomarker in predicting the efficacy of neoadjuvant chemotherapy in the study of Fersching et al 50 Specifically, apoptosis inducted by PAI-1 in vascular cells is associated with anti-adhesive characteristics via the caspase 3 signaling pathway, which is demonstrated in the report of Al-Fakhri et al 51 Furthermore, compared with the blank and siRNA-NC groups, the length and weight of thrombus were decreased in both the miR-335-5p mimics and siRNA-PAI-1 groups. Bonemarrow-derived endothelial progenitor cells (EPCs) play an important role in the new vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…44 Through analysis with CCK-8 and flow cytometry, augmented proliferation and attenuated apoptosis were determined in femoral vein endothelial cells when miR-335-5p expression was up-regulated and PAI-1 expression was down-regulated. MiR-335-5p has been reported to be involved in cell differentiation and apoptosis of osteoblasts in diabetic osteoporosis, 47 In addition, miR-335 has the ability to influence apoptosis and invasion in non-small cell lung cancer, 48 and clear cell renal cell cancer proliferation and invasion by inhibiting the expression of BCL-W. 49 Meanwhile, PAI-1 is proved to be an apoptosis-related biomarker in predicting the efficacy of neoadjuvant chemotherapy in the study of Fersching et al 50 Specifically, apoptosis inducted by PAI-1 in vascular cells is associated with anti-adhesive characteristics via the caspase 3 signaling pathway, which is demonstrated in the report of Al-Fakhri et al 51 Furthermore, compared with the blank and siRNA-NC groups, the length and weight of thrombus were decreased in both the miR-335-5p mimics and siRNA-PAI-1 groups. Bonemarrow-derived endothelial progenitor cells (EPCs) play an important role in the new vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-30B levels in these subjects are correlated with the genotype of the rs2234693 SNP in the estrogen receptor- α gene ( ESR1 ). Furthermore, females with schizophrenia have less severe deficits in cognitive parameters, such as memory, compared to males [ 143 ], and both miR-30B and ESR1 have been shown to be important for cognitive function [ 144 , 145 , 146 , 147 ]. Thus, miR-30B warrants further study to understand whether it may be protective against cognitive deficits seen in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Singh et al (46) reported that miR-200c directly regulates the expression of dual specificity protein phosphatase 1, downregulates the activity of the mitogen-activated protein kinase signaling pathway and promotes cardiomyocyte hypertrophy. Based on the results of a study investigating the regulation of PAI-1 by miRNA (47), the present study used bioinformatics to identify the miRNA that regulates PAI-1 expression; the results indicated that miR-30b regulates PAI-1. Previous studies have demonstrated that miR-30b affects the Figure 7.…”
Section: Discussionmentioning
confidence: 99%